Urban artistic interventions: A typology of artistic political actions in the city. (June 2022) - Hoop, Marie; Kirchberg, Volker; Kaddar, Merav; Barak, Nir; de Shalit, Avner
Abstract: How do critical artists intervene in urban space, and why? This question is explored in an interurban fieldwork study examining artistic interventions in four cities: Hanover and Hamburg in Germany, and Tel Aviv-Jaffa and Jerusalem in Israel. Grounded on a plethora of artistic interventions gathered in these cities, the article proposes a typology based on techniques, goals, sociability degrees and relations to urban space. On the one hand, urban artistic interventions vary from a compensatory improvement of social conditions to a highly political and protest-driven irritation of existing urban power structures and processes. On the other, the discourses behind the different modes of urban artistic intervention reveal similarities, bringing recurring concepts of "art in public space" to the forefront and referring to similar lines of reasoning which guide urban artists in their practice. This article extends the existing literature by offering a typology of artistic interventions in urban space, highlighting the critical agency of urban artists. Highlights: Artistic Interventions. Urban Art. Political Art. Typology. Inter-urban fieldwork.